Reformasi Birokrasi Indonesia: Peluang dan Hambatan - Yusriadi, Yusriadi (Universitas Medan Area, 2018)
The 1998 political reform was the gateway to Indonesia towards a new history in the dynamics of national politics, which could go hand in hand with bureaucratic reform. Great changes are expected in the design of life in the community, nation, and state, concerning dimensions of political, social, economic and cultural life. In order to implement the acceleration in the implementation of reforms in Indonesia well, the government implemented nine programs to reach 8 regions which were the objectives of implementing the grand design of bureaucratic reform. One form of bureaucracy reform is innovation, like e-government which has a positive impact on good governance. The journey of bureaucratic reform in Indonesia is not without dignity, facts show, a government that is still full of nuances of Corruption, collusion, and nepotism. This paper describes opportunities and obstacles to bureaucratic reform in Indonesia.